Metagenomic insights into enhancing protein content and digestibility in Jack Bean (Canavalia ensiformis) tempeh: Unraveling microbial dynamics during fermentation - Vira Putri Yarlina; Mohammad Djali; Robi Andoyo; Siti Nurmilah; Mohd Nizam Lani (Applied Food Research)
Jack beans (Canavalia ensiformis) are a locally abundant Indonesian bean variety boasting a significant protein content that remains underutilized. The production of tempeh from Jack beans presents a promising avenue for tapping into this valuable vegetable protein source. The tempeh-making process involves several key stages, including soaking the ingredients, inoculating with a mold starter, and fermenting the mixture. Throughout each stage, protein content preservation and effective utilization are paramount. This study uses high-throughput sequencing technologies to characterize protein hydrolysis in Jack beans during fermentation. The research aims to investigate how microorganisms participating in the fermentation of Jack bean tempeh influence protein content and protein digestibility. The findings reveal that prolonging the fermentation time of Jack beans, utilizing a 1.5 % tempeh mold starter, and fermenting for 36 h resulted in a notable increase in protein content by 66.63 % and enhanced protein digestibility in vitro by 48.82 %. This improvement may be attributed to the predominant activities of Bacillus and Rhizopus during the fermentation process by the metagenomics approach.